Cervical Myelopathy Caused by Os Odonteideum: Case Report - Cengiz Bahadır,; Vildan Yaman,; Aslıhan Taraktaş, (Archives of Rheumatology, 2009)
Congenital anomalies of the odontoid process have been described in the literature. Os odonteideum is a seperate odontoid process from the body of the axis. It is the most common anomaly of the odontoid process. It may cause cervical instability, atlontoaxial dislocation and myelopathy. Os odontoideum must be distinguished from an acute fracture of the dens. In this report, a case with os odontoideum complicated with asymptomatic myelopathy and cervical disc herniation was discussed. (Turk J Rheumatol 2009; 24: 53-5)